Kinetic model describing the UV/H2O2 Photodegradation of phenol From water (2017)
ABSTRACT: A kinetic model for phenol transformation through the UV/H2O2 system was developed and validated. The model includes the pollutant decomposition by direct photolysis and HO, HO2 and O2 - oxidation. HO scavenging effects of CO32-, HCO3-, SO42- and Cl- were also considered, as well as the pH changes as the process proceeds. Additionally, the detrimental action of the organic matter and reaction intermediates in shielding UV and quenching HO was incorporated. It was observed that the model can accurately predict phenol abatement using different H2O2/phenol mass ratios (495, 228 and 125), obtaining an optimal H2O2/phenol ratio of 125, leading to a phenol removal higher than 95% after 40 min of treatment, where the main oxidation species was HO. The developed model could be relevant for calculating the optimal level of H2O2 efficiently degrading the pollutant of interest, allowing saving in costs and time.